Recycling Treatment Plant Residuals: Concerns Beyond Pathogens. Issue 6 (2nd June 2020) - Duke, Aaron W.; Roth, Damon K.; Gross, Mark; Jin, Shanshan
Key Takeaways: As the practice of recycling water treatment residuals matures, additional contaminants beyond pathogens are becoming increasingly relevant to how facilities may recycle their residuals streams. Manganese recycling and residuals treatment will become more critical if the US Environmental Protection Agency (USEPA) ultimately promulgates a primary drinking water regulation targeting manganese. If a facility implements onsite dewatering and subsequently recycles their residuals streams, they may need to reduce the polyacrylamide levels to comply with USEPA regulations.